2001
DOI: 10.1126/science.1066273
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increase in Clusters of Presynaptic Proteins at Onset of Long-Lasting Potentiation

Abstract: A change in the efficiency of synaptic communication between neurons is thought to underlie learning. Consistent with recent studies of such changes, we find that long-lasting potentiation of synaptic transmission between cultured hippocampal neurons is accompanied by an increase in the number of clusters of postsynaptic glutamate receptors containing the subunit GluR1. In addition, potentiation is accompanied by a rapid and long-lasting increase in the number of clusters of the presynaptic protein synaptophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
128
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 27 publications
18
128
1
Order By: Relevance
“…One other possibility is that cGK may act synergistically with Ca 2ϩ that enters the presynaptic terminal during the weak tetanus, perhaps by converging on a common molecular target. Consistent with that possibility, Antonova et al (2000) recently found that the NO-cGMP-cGK pathway contributes to an increase in the number of synaptophysin-and synapsin-immunoreactive presynaptic terminals during long-lasting potentiation in hippocampal cell culture. Those results provide independent evidence that cGK acts presynaptically and indicate that it in some way affects vesicleassociated proteins.…”
Section: Discussionmentioning
confidence: 52%
“…One other possibility is that cGK may act synergistically with Ca 2ϩ that enters the presynaptic terminal during the weak tetanus, perhaps by converging on a common molecular target. Consistent with that possibility, Antonova et al (2000) recently found that the NO-cGMP-cGK pathway contributes to an increase in the number of synaptophysin-and synapsin-immunoreactive presynaptic terminals during long-lasting potentiation in hippocampal cell culture. Those results provide independent evidence that cGK acts presynaptically and indicate that it in some way affects vesicleassociated proteins.…”
Section: Discussionmentioning
confidence: 52%
“…Glutamate is the major excitatory neurotransmitter in the hippocampus and mediates the neuronal response through CREB activation and LTP formation, eventually leading to synapse development and strengthening. In vitro studies on cultured hippocampal neurons (14,15) have used brief glutamate stimuli to investigate the biochemical changes that underlie synaptic strength modification. We found that cultures pretreated for 2 h with 5 M A␤ showed a 40-45% decrease in CREB phosphorylation in response to treatment with 50 M glutamate for 15 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in clinical practice most patients who achieve an initial response to antibody treatment generally acquire resistance within 1 year [6]. HER-2 transmits information from breast cancer cell surface into cytoplasm and is crucial in growth inhibition and cellular adhesion [7]. Breast cancer cells overexpressing HER-2 and CD44 receptors tend to be much more elastic than normal cells, as they exhibit a much stiffer extracellular matrix (ECM) [8].…”
Section: Introductionmentioning
confidence: 99%